FIELD TESTS OF THE PROTOTYPE OF THERMOELECTRIC SYSTEM FOR THERMAL INFLUENCE ON THE LEVEL OF THE MIDDLE THIRD OF THE SHOULDER OF THE MAN - T. A. Ismailov; O. V. Evdulov; R. A.-M. Magomadov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In this work the results of field tests of the prototype of thermoelectric system for thermal influence on the level of the middle third of the shoulder of the person, enabling the treatment and prevention of diseases of musculoskeletal system without medical intervention. Given the design of the device, experimental stand, and also a technique of field tests of the system. Presents thecharacteristics of a prototype thermoelectric systems, recorded using the measuring bench.